PECULIARITIES OF IDENTIFYING CAPILLARIIDES PARASATIZING IN POULTRY - Melnychuk, V. V.; Yevstafieva, V. O.; Borodai, Ye. O.; Lozhkina, O. V. (Scientific Progress & Innovations, 2020)
Nematodes of Capillariidae Neveu-Lemaire family, 1936 belong to a large and widespread group of par-asitic helminthes, which can be localized in almost all host organs. Different species parasitize in monkeys, wild and domestic carnivores, domestic ruminants, rodents, marsupials, fish, amphibians, as well as humans. Some of them are highly pathogenic and have not only epizootological but also epidemiological significance. The results of morphological studies play an important role in practical taxonomy for the construction of the natural system of this group of nematodes, as well as for understanding the evolution and phylogeny of Capillariidae. Due to such analysis, a generalized picture of the structure and anatomical organization of capillariides is created. The research was conducted at the laboratory of the Department of Parasitology and Veterinary Sanitary Expert Examination of Poltava State Agrarian Academy. The aim of the study was to establish differential species morphological and metric features of capillariides isolated from poultry. Ac-cording to the results of morphological studies of Capillaria anatis (Schrank, 1790) Travassos, 1915 and Baruscapillaria obsignata (Madsen, 1945), Moravec, 1982, mature males and females, their significant simi-larity was noted. These species have the same general body structure: in females ̶ the structure of the vulva, vagina, in males ̶ the structure of the tail end. At the same time, the differential morphological feature of C. anatis is the presence of spines on the spicular vagina. Significant differences in morphometric parame-ters of male and female capillariides of B. obsignata and C. anatis species were determined, which will ena-ble to increase the effectiveness of their identification. Morphometric parameters of B. obsignata males were higher than those of C. anatis in five indicators, which characterized the body and spicules length, the pseu-dobursa width and length. At the same time, the spicule of C. anatis is wider throughout its length than that of B. obsignata. In B. obsignata and C. anatis females, seven metric indicators have a significant difference in values, of which according to four indicators (body width in the vulva region; length, width and thickness of the egg membrane) females of C. anatis had higher parameters than those of B. obsignata. Differential features include the presence of cuticular elevations in the vulva of B. obsignata.